Financial Data Warehousing at Village Credit Institution xyz Using a Star Schema - Sandhiyasa, I Made Subrata; Nopianti, Ni Kadek Winda; Nugraha, Putu Gede Surya Cipta (Jurnal Galaksi, 2025)
The role of information technology is the main focus in financial management, especially in supporting the data analysis process for effective decision making.  Village Credit Institution xyz, as a financial institution owned by Pekraman Villages in Bali, faces obstacles in presenting financial data that is still in the form of tables. The presentation is not effective in providing a clear and adequate picture to support management decision-making. Makes it difficult to identify customers with bad or current credit. This research aims to build a financial data visualization system at  Village Credit Institution  xyz using Looker Studio, with a data warehouse design implemented using Kimball's Nine Steps method. The ETL process is carried out using Pentaho Data Integration (PDI) to compile data from various sources. The final result of this research is data visualization in the form of 9 main menus. This system allows the presentation of data in the form of interactive graphs, thus facilitating data analysis, accelerating the decision-making process, and increasing the efficiency of financial data management in  Village Credit Institution. System testing was conducted using the User Acceptance Testing (UAT) method with a result of 92.48% or strongly agree, indicating that the developed system has met the needs of users.